INNOVATIVE MARKETING CONCEPTS IN THE CONTEXT OF GREEN ECONOMY (Marketing Jurnali, 2025)
This article analyzes the theoretical foundations of green marketing concepts and its impact on the environment and economy. The necessity, advantages and core principles of eco-friendly products and environmentally conscious brands are examined, and Patagonia is taken as a case example.